Dietary Selenium Reduces the Toxic Effect of Mercury on Different Organs (Brain, Gills, Kidney and Liver) of Rohu Fish (Labeo rohita) - Khan, Muhammad Xaaceph; Anum, Beenish; Bibi, Ruqia; Babar, Masroor Ellahi; Ashraf, Muhammad; Ramzan, Amera; Aihetasham, Ayesha; Abbas, Syed Hassan (BioScientific Review, 2021)
Due to improbably high partiality of antioxidant selenium to mercury, selenium isolates mercury and reduces its biological handiness to organisms. The current study investigates the effect of mercury (Hg) and selenium (Se) on the fingerling of Labeo rohita. Various sub-lethal concentrations of Hg including 0.125μg/g, 0.250μg/g, and 0.500μg/g were used and incorporated in fish diet with a commercial diet plan (fish meal 40%, soya bean 33%, 3% of vitamins premix, mineral premix and oil each and rice polish 18%). To understand how Se reduces the toxic effect of Hg, fingerlings were exposed to 6ug/g Se singly and combined with doses of Hg. The effect of these heavy metals was observed after 24, 48, 72, and 96 hours on different organs (brain, gills, kidney and liver) of L. rohita. The organs of the exposed rohu fish showed significant changes in their microscopic anatomy in comparison to control. Prominent changes were observed in Hg treatments and these included embody shrinkage of capillary and dilation of the hollow lumen. In addition to the aforementioned changes, vacuolation, peeling, hydropic swelling, and hyaline degeneration of hollow epithelium were also observed. Moreover, cysts and hamorrhage developed in the organs of the fish. The length of exposure seemingly has a profound impact on organs because the increase in length of exposure enhanced the severity of histopathological damages. However, combined doses of metals caused reduction in the toxicity of mercury, resulting in decreased damage in the shrinkage of capillary and dilation of the hollow lumen. During the histological study, vacuolation, hydropic swelling, and hyaline degeneration of the hollow epithelium were also reduced. For Hg, lethal concentration (LC50) was 0.374ug/g. However, when Hg and Se were combined, LC50 dropped to 0.491ug/g. The results of this study suggest that exposure to Se helps to scale back the impact of Hg on the mortality and different organs of L. rohita fingerling. Keyword: brain, gills, kidney, Labeo rohita, liver, mercury (Hg), selenium (SE) Copyright (c)The Authors